Mitochondrial dysfunction in cellular senescence - Solomko, L.; Kussainova, A.; Bulgakova, О. (Fundamental and Experimental Biology, 2025)
Cellular senescence is a complex process characterized by cell cycle arrest and loss of cell division ability. While the process of aging is the result of numerous molecular mechanisms, mitochondria play a pivotal role in its progression. Mitochondrial dysfunction, indicated by impaired respiratory capacity and a diminished energy status of the cell, is frequently accompanied by an augmented production of free oxygen radicals, resulting in oxidative stress. This condition not only accelerates cellular aging, but also its progression. A substantial body of research has substantiated the association between mitochondrial dysfunction and cellular senescence, underscoring the significance of mitochondria as a target for anti-aging therapies and interventions. The process of aging is associated with the onset of various age-related diseases, including cancer, cardiovascular diseases, and neurodegenerative diseases. A comprehensive understanding of these mechanisms offers novel opportunities to develop effective strategies that can mitigate the effects of senescence. This article will provide a comprehensive overview of the mechanisms contributing to mitochondrial dysfunction during the senescence process. In addition, it will offer a detailed review of the major consequences of this dysfunction, with a particular focus on its impact on cellular senescence.